Predictors of quality of life in bipolar disorder: A path analytical study. (March 2020) - Cotrena, Charles; Branco, Laura Damiani; Shansis, Flávio Milman; Fonseca, Rochele Paz
Highlights: QoL was directly predicted by depression symptoms and a diagnosis of BD. (Hypo)manic symptoms indirectly predicted QoL through depressive symptoms. Cognitive reserve predicted social QoL more significantly than a diagnosis of BD. Treating depression symptoms and increasing cognitive reserve may improve QoL in BD. A diagnosis of BD and/or substance use disorders were risk factors for poor QoL. Abstract: Quality of life (QoL) is an important outcome in psychiatric illnesses like bipolar disorder (BD). However, little is known about the variables that affect it, and therefore contribute to prognosis and treatment outcomes in these populations. This study aimed to explore QoL in BD and investigate its relationship with modifiable (cognitive reserve, cognitive ability, mood symptoms) and non-modifiable factors (diagnosis, previous suicide attempts, substance misuse, age). The WHOQOL-bref was administered to 121 control participants and 109 patients with BD, who also underwent clinical and neuropsychological assessments. Factor analysis was used to identify latent constructs underlying WHOQOL-bref domains, and structural equation models were used to examine predictors of each latent construct. Two latent constructs were identified in the WHOQOL-bref, and labeled 'Personal' and 'Social' QoL. Both were directly predicted by depression symptoms and a diagnosis of BD, and indirectly predicted by (hypo)manic symptoms. Cognitive reserve was a stronger predictor of social QoL than a diagnosis of BD. Our findings suggest that the management of depression symptoms and fostering of cognitive reserve may improve QoL in BD. A diagnosis of BD and/or substance use disorders were risk factors for poor QoL, and may signal the need for preventive interventions to promote well-being.